F.R. David : Recto Verso. - Holder, Will; Abbott, Paul; Baber, Phil; Day, Jeremiah; Gordon, Melissa; Gruijthuijsen, Krist; Handley, Sarah; Mayer, Cathrin; Mihaylova, Snejanka; Our Polite Society; Paldi, Livia; Quesney, Suzanne; et al. ([s.l.] : uh books with Kw Institute for Contemporary Art, 2019)
Gruijthuijsen, Krist ; Abbott, Paul ; Baber, Phil ; Alighieri, Andrea di Serego ; Day, Jeremiah ; Gordon, Melissa ; Handley, Sarah ; The Lake Radio ; Mayer, Cathrin ; Mihaylova, Snejanka; Our Polite Society ; Paldi, Lívia ; Quesney, Suzanne ; von Zweigbergk, Felicia
boek